Urgence of Halal Food and Drink Education: Review Economic Interpretation And Hadith - Ahmad Mahfudzi Mafrudlo; Dudi Nasrudin; Zuhratul Aini Mansur (Journal of Halal Product and Research (JHPR), 2022)
Consumption, which is an important need and a special variable in human life, often has negative implications when it is released without any regulation. The religious elements contained in it have provided limits for the creation of a balance of life. Namely the concept of halal and thayyib in food and drink according to Islam. So that a deep understanding is needed to educate through the interpretation of economic verses, especially about consumption. This paper seeks to explore the urgency of halal food and drink, which then makes it the basis and pattern of life for Muslims. By using the interpretation method to analyze the urgency, and provide a model in the education of halal food and beverages. Three patterns of implications for halal consumption trends have provided a balanced condition according to Islam. Namely first: objects that have become a trend to provide good habits, second: elements of benefit and benefits that exist in halal food and drinks, third: do not have a negative impact and harm to the body and soul. This paper also finds the term education which is the basic element of the halal trend in food and beverages. Keywords: Halal, thayyib, education, life balance